The Contribution Of Control Mechanisms In Combating Fraudulent Practices Related To Corruption In The Banking Sector: A Case Study Of The Implementation Of ISA 240 Standard (Journal of Namibian Studies : History Politics Culture, 2023)
Corruption distorts the decisions of economic agents, discourages investors, and heavily impedes a country's progress by diverting public resources for private gain.To combat fraud and corruption, it is necessary to implement a combination of control mechanisms, including the use of auditing methods, continuous monitoring, compliance procedures, operational controls, and any other control tools within the framework of internal control, specifically targeting the fraud that occurs in the banking sector.It is important to note that the ISA 240 standard does not guarantee the detection of all frauds, as some frauds can be sophisticated and intentionally concealed. However, by providing clear guidance and strengthening fraud-related audit procedures, the standard aims to improve the overall quality of audits and enhance public trust in financial statements.Our article will provide an overview of this offense while highlighting various definitions of potential frauds and the relevance of organizational theories and their correlation with fraud and corruption. The article will also identify the prioritization of controls within entities within the banking system, as well as the shortcomings and gaps in control within financial organizations.